ANALISIS KONTRIBUSI RETRIBUSI DAERAH DAN LABA BUMD TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI PROVINSI KALIMANTAN SELATAN - MUHAMMAD LAZUARDI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study aims determine the level of contribution and effectiveness of regional retribution and profit of regional owned enterprises to LOR as well as efforts that can be done to improve the acceptance of regional retribution and profit of regional owned enterprises in South Kalimantan Province. The research method used is descriptive quantitative method. The results of this study indicate that the contribution of regional retribution and profits of regional owned enterprises to LOR in South Kalimantan Province from 2014-2016 is still low. In the 2014-2016 period the results of the effectiveness of regional retribution and regional owned enterprises were very effective.This means that the realization of regional levies and profits of regional owned enterprises in the 2014-2015 period always reaches the target. Then efforts can be made to increase revenues as well as the contribution of regional retribution to LOR, namely through intensification and extensification.While the effort to increase the revenue of regionally owned enterprises is through rearrangement and improvement of company management, training or coaching of regional owned enterprises employees.Keywords: Contribution, Effectiveness, Regional Retribution, Profit of Regional Owned Enterprises and Local Own Revenue